Samoreguljacija psichologiceskogo sostojanija sportsmenov vyssej kvalifikacii - Bondarcuk, T. V.; Potapov, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The revealed and described in the article retrospective analysis of the scientific and scientific-methodical literature in psycho-pedagogical, psycho physiological areas of correction of a mental condition has allowed the author to allocate the basic tendencies, prospects and the actual problems connected to the self-control of the mental condition of elite athletes.